EFEKTIVITAS LAYANANBIMBINGAN KELOMPOK MENGGUNAKAN METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII SMP NEGERI 2 LABUHAN HAJI - Nurhadia; Yunitasari, Dukha; Zain, Maulidiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of group guidance services using the Problem-Based Learning method in improving the learning motivation of 7th-grade students at SMP Negeri 2 Labuhan Haji. The study employs a quantitative approach using a quasi-experimental design, specifically the non-equivalent control group design. The population consisted of 7th-grade students at SMP Negeri 2 Labuhan Haji, while the sample comprised 16 students, 8 from class VII-A (experimental group) and 8 from class VII-B (control group) selected using purposive sampling. Data were collected using a learning motivation questionnaire and analyzed using normality tests, homogeneity tests, and the Independent Sample t-Test with the aid of SPSS version 23. The results indicate that the average learning motivation score of the experimental group increased from 51.63 to 72.50, whereas the control group increased from 53.13 to 58.13. Hypothesis testing yielded a t-value of 12.269 with a significance (2-tailed) value of 0.000 (<0.05); consequently, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Thus, it can be concluded that group guidance services using the Problem-Based Learning method are effective in improving the learning motivation of 7th-grade students at SMP Negeri 2 Labuhan Haji. Keywords: Group Guidance Services, Problem-Based Learning, Learning Motivation